HBM4EU Diisocyanates Study-Research Protocol for a Collaborative European Human Biological Monitoring Study on Occupational Exposure - Jones, Kate (2022)
Funding: This work has received external funding from the European Union’s Horizon 2020 research and innovation program under grant agreement No. 733032 and received co-funding from the author’s organizations and/or Ministries.